Nicotine Alters the Proteome of Two Human Pancreatic Duct Cell Lines - Paulo, Joao A (JOP. Journal of the Pancreas, 2014)
Context Cigarette smoking is a known risk factor of pancreatic disease. Nicotine - a major cigarette tobacco component - can traffic through the circulatory system and may induce fibrosis and metastasis, hallmarks of chronic pancreatitis and pancreatic adenocarcinoma, respectively. However, at the biomolecular level, particularly in pancreatic research, the effects of nicotine remain unresolved. Methods The effects of nicotine on the proteomes of two pancreatic duct cell lines–an immortalized normal cell line (HPNE) and a cancer cell line (PanC1)- were investigated using mass spectrometry-based proteomics. For each cell line, the global proteomesof cells exposed to nicotine for 24 hrswere compared with untreated cells in triplicate using 6-plex tandem mass tag-based isobaric labeling techniques. Results Over 5,000 proteins were detectedper cell line. Of these, over 900 proteins were differentially abundant with statistical significance (corrected P-value <0.01) upon nicotine treatment, 57 of which were so in both cell lines. Amyloid precursor protein, previously observed to increase expression in pancreatic stellate cells when exposed to nicotine, was also up-regulated in both cell lines.In general, the two cell lines varied in the classes of proteins altered by nicotine treatment, supporting published evidence that nicotine may play different roles in the initiation and progression of pancreatic disease. Conclusions Understanding the underlying mechanisms associating nicotine with pancreatic function is paramount to intervention aiming to retard, arrest, or ameliorate pancreatic disease. Image: Heat map of 315 proteins that were statistically significant in the HPNE cell line.